2020 IEEE Conference on Virtual Reality and 3D User Interfaces (VR) 2020
DOI: 10.1109/vr46266.2020.00082
|View full text |Cite
|
Sign up to set email alerts
|

The Space Bender: Supporting Natural Walking via Overt Manipulation of the Virtual Environment

Abstract: Manipulating the appearance of a Virtual Environment to enable natural walking has so far focused on modifications that are intended to be unnoticed by users. In our research, we took a radically different approach by embracing the overt nature of the change.To explore this method, we designed the Space Bender, a natural walking technique for room-scale VR. It builds on the idea of overtly manipulating the Virtual Environment by "bending" the geometry whenever the user comes in proximity of a physical boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…We conducted a within-subjects study with 20 participants comparing our foldable techniques against each other as well as an adapted implementation of a similarly situated base condition, Stop&Reset [8,20,31]. Our results indicate that Accordion provided the most continuous and natural experience of walking among the four evaluated techniques, in addition to being conducive towards orientation and being ranked first in terms of user preference.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We conducted a within-subjects study with 20 participants comparing our foldable techniques against each other as well as an adapted implementation of a similarly situated base condition, Stop&Reset [8,20,31]. Our results indicate that Accordion provided the most continuous and natural experience of walking among the four evaluated techniques, in addition to being conducive towards orientation and being ranked first in terms of user preference.…”
Section: Introductionmentioning
confidence: 92%
“…Additionally, subtle redirection techniques manipulating the architecture of the VE are typically based on indoor rooms or self-contained spaces within a larger VE, without visual connections (e.g., via windows or terraces) throughout the space in order to hide the technique's intervention in the environment [26]. In contrast, 'overt' manipulation tends to be more flexible in terms of both spatial constraints and the representation of the VE [20,27,31], at the risk, however, of inducing a lower sense of presence in participants.…”
Section: Introductionmentioning
confidence: 99%
“…Rietzler et al [45] confirmed that users could accept curvature gains far beyond perceptual thresholds in RDW. Simeone et al [50] designed another overt walking technique in the context of room-scale VR, which was faster and preferable than compared techniques. Concurrently, Telewalk [44] combined observable translation and curvature gains to allow endless virtual walking along a real-world path with a pre-defined radius.…”
Section: Overt Manipulationmentioning
confidence: 99%
“…The concept of alignment in the context of redirected walking was first formally studied by Thomas et al [37,39]. However, Zmuda et al [43] used key elements of alignment prior to the work of Thomas et al Additionally, Simeone et al [31] recently introduced a locomotion technique that is similar to alignment in that it aims to match the VE and the PE, but it does so by overtly manipulating the VE in real time. In this section, we define our notion of alignment and provide the details of our general alignment-based redirection controller.…”
Section: Redirection By Alignmentmentioning
confidence: 99%